2016
DOI: 10.1097/dbp.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Association of Markers of Cholesterol Synthesis with Disturbed Sleep in Smith-Lemli-Opitz Syndrome

Abstract: OBJECTIVE Smith-Lemli-Opitz syndrome (SLOS) is a rare genetic disorder characterized by cholesterol synthesis impairment. A host of physical, developmental, and behavioral presentations are associated with SLOS, many of which have been related with disorder severity. Sleep disturbance is commonly reported in SLOS. The current study is the first to examine the association between sleep disturbance and biomarkers of cholesterol synthesis defect. METHODS Twenty youth with SLOS participated. Biomarkers of choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…7-DHC-derived oxysterols most likely influence normal brain development and function [14]. It has been suggested that cholesterol deficiency and/or precursor accumulation might influence behavior, including altered sleeping patterns [34,35]. Skin photosensitivity, a common dermatological finding in SLOS patients, might be the consequence of 7-DHCderived oxysterols [36].…”
Section: Discussionmentioning
confidence: 99%
“…7-DHC-derived oxysterols most likely influence normal brain development and function [14]. It has been suggested that cholesterol deficiency and/or precursor accumulation might influence behavior, including altered sleeping patterns [34,35]. Skin photosensitivity, a common dermatological finding in SLOS patients, might be the consequence of 7-DHCderived oxysterols [36].…”
Section: Discussionmentioning
confidence: 99%